FEATURES OF DEVELOPMENT OF THE SYSTEM OF STIMULATION OF INNOVATION ACTIVITY OF ENTERPRISES IN TODAY'S CONDITIONS - Юрій Шпак; Ігор Процайло; Андрій Мороз (Економіка та суспільство)
The process of stimulating innovation can take place at the macro level, that is, at the national level, at the meso-level, that is, taking into account the sectoral methods of activation and, in particular, at the micro level, through the introduction of tools for activating the personnel of enterprises to creative, creative, rationalizing activities. The article presents the forms and methods of stimulation of innovation activity in the organization. The influence of the incentive system on the expansion of innovative opportunities and strengthening the competitiveness of the business structure is studied. Also focuses on the directions of stimulation of innovation activity of industrial enterprises, which include a whole range of measures that provide for the formation of organizational, motivational and financial mechanisms for intensifying creative searches among employees of enterprises, as well as stimulating managers to start and develop such activities in today's conditions. The article provides an analytical characteristic of a specific enterprise DP Air Gas LLC, presents the results of a study of its innovation activity in dynamics and offers recommendations for the development of a system of stimulation of innovation activity by its activation at the enterprise Among the main tasks was the development and adoption of sound management decisions to stimulate innovation, solving existing problems in this area, in particular at DIPI Air Gas LLC, and analytical substantiation of the proposed measures to stimulate the innovation activity of industrial enterprises, in particular DIPI Air Gas LLC.